The Silence of Garments - Giuppy D'Aura (Aisthema: International Journal, 2021)
Different societies have traditionally conveyed status in different ways. Elegance is one of the examples through which modern and capitalistic societies express it. Based on subtraction and understatement, the practice of elegance is at the cross road between several aspects: class, gender, morality and taste. As this essay will explain, the emergence of elegance during Modernity is to be found in the very same elements and moral attitudes that generated capitalism. For this reason, this essay will delve into the analysis of the emergence of capitalism provided by Max Weber which will be considered against some of the most influential works written about fashion during the 20th Century, aiming not only to define the rules of elegance and its origins, but also its functions. Elegance is the favoured child of modern capitalism as it fulfils its contradictory needs of display and understatement.